Efektivitas Program Pemberdayaan Masyarakat Berbasis Rukun Warga (PMB-RW) Dalam Mewujudkan Prinsip Tridaya Di Kota Pekanbaru - Ema Fitri Lubis; Evi Zubaidah (UIR Press, 2019)
The PMB-RW Program aims to create and improve the quality of community life, both individually and in groups to participate in solving various problems related to efforts to improve the quality of life, independence, and community welfare. The purpose of this research is: To find out how the effectiveness of Community-Based Community Empowerment Program (PMB-RW) in Realizing Tridaya Principles in Pekanbaru City. And to analyze what are the factors that influence the Effectiveness of Community-Based Community Empowerment Program (PMB-RW) in Realizing Tridaya Principles in Pekanbaru City. This research uses qualitative research with descriptive methods. The findings of this study based on the indicators used are 1. The PMB-RW program process is seen from the communication, decision making, employee development until the socialization has been carried out because this program has been started from 2014. 2. The efficiency of the PMB-RW program is still considered ineffective. 3. Satisfaction of PMB-RW Program which is assessed from the level of apparatus performance, and the level of public / community. 4. The excellence of the PMB-RW program is judged by its satisfaction, consistency, and bureaucratic structure. 5. Development of PMB-RW programs that refer to intervention strategies and achievement of objectives.